G3P2A0 Hamil 32 Minggu dengan Hipertensi Gestasional - ardinda arlindova; Shariff, Fonda Octarianingsih (Medula, 2025)
Hypertension in pregnancy is defined as an increase in blood pressure ≥140/90 mmHg that appears after 20 weeks of gestation without a history of previous hypertension. This case report discusses the case of a 39-year-old woman (G3P2A0) with a gestational age of 32 weeks who was diagnosed with gestational hypertension. The patient was referred from a health center with a history of high blood pressure during ANC (Antenatal Care) and recurrent headaches since 20 weeks of gestation. Examination showed blood pressure of 157/91 mmHg without signs of severe preeclampsia, while proteinuria +1 was detected. Risk factors include age >35 years and a history of hypertension in previous pregnancies. The patient was given pharmacological therapy, namely nifedipine 10 mg 1x1 orally with regular blood pressure monitoring. This study emphasizes the importance of early detection and management of gestational hypertension to prevent complications for the mother and fetus.